Treatment outcomes and associated factors among extremely preterm infants in a major children hospital in Guangxi, China - Yan Li; Qiu-fen Wei; Dan-hua Meng; Xin-nian Pan; Yan Mo; Li-ping Yao; Lian-fang Jing; Dan Zhao; Kai-yan Shen; Jing Xu (Pediatrics and Neonatology)
In developing countries, infant survival rate and long-term outcomes of extremely preterm infants(EPIs) have significantly improved due to advances in perinatal care. The striking gap in the treatment outcome of EPIs between China and the other developed countries was a major concern. To assess treatment outcomes and associated factors among EPIs in Nanning, China. Methods: This was a perspective study consisting of eligible cases with gestational age between 22 and 28 weeks and infants were followed to 18–24 months of age. Data including clinical characteristics, perinatal factors and after-birth conditions were collected from the neonatal intensive care unit (NICU) in a major women's and children's health hospital in Guangxi Province from January 1st 2010 to February 1st 2015. Results: During that period 79 EPIs were born in the hospital. Twenty-eight infants died in hospital after their parents decided to withdraw clinical treatment. Of the 51 surviving infants, 5 infants were lost to follow-up. Eleven of the 46 infants were evaluated at 18–24 months of age and were diagnosed with neurodevelopmental disability and 35 infants showed normal motor language development. The incidence of intrauterine infection and intraventricular hemorrhage (IVH) grade III were both higher in the group of infants who were diagnosed neurodevelopmental disability than in the group of infants with normal motor language development (p < 0.05). Logistic regression analysis showed that intrauterine infection (OR = 33.290, 95%CI = 2.180–508.351) and IVH grade III (OR = 26.814, 95%CI = 3.631–197.989) were the major risk factors for neurodevelopmental disability in EPIs. Conclusions: Intrauterine infection and IVH grade III were associated with the neurodevelopmental disability in EPIs.